2021
DOI: 10.1002/jcop.22690
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, anger, and mindfulness as predictors of general health in the general population during COVID‐19 outbreak: A survey in southeast Iran

Abstract: Communities have been exposed to the complications and problems caused by COVID‐19 disease, which has had various and complex effects on general health. The aim of this study was to investigate the relationship between anxiety, anger, mindfulness, and general health in the general population during the COVID‐19 outbreak in Iran. This cross‐sectional study was performed on 456 participants from September 2020 to April 2021. For data collection, Demographic Characteristics Form, General Health Questionnaire, Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Emerging evidence from studies on the COVID-19 pandemic or similar disasters, suggests that several factors are implicated in the development of mental health and anxiety symptoms; for example, sociodemographic characteristics, such as age, gender, or receiving inadequate social support have significantly impacted mental health outcomes during such difficult times [ 5 , 12 , 13 , 14 ]. Additionally, having an infected family member with COVID-19 or excessive fear of becoming infected were also associated with stress-related symptoms [ 14 , 15 , 16 ]. Furthermore, having an existing mental health condition such as depression or anxiety may present an additional risk, which may contribute to potential exacerbation of the symptoms or relapsing due to service disruption or the need for isolation [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence from studies on the COVID-19 pandemic or similar disasters, suggests that several factors are implicated in the development of mental health and anxiety symptoms; for example, sociodemographic characteristics, such as age, gender, or receiving inadequate social support have significantly impacted mental health outcomes during such difficult times [ 5 , 12 , 13 , 14 ]. Additionally, having an infected family member with COVID-19 or excessive fear of becoming infected were also associated with stress-related symptoms [ 14 , 15 , 16 ]. Furthermore, having an existing mental health condition such as depression or anxiety may present an additional risk, which may contribute to potential exacerbation of the symptoms or relapsing due to service disruption or the need for isolation [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, having an infected family member with COVID-19 or excessive fear of becoming infected were also associated with stress-related symptoms [ 14 , 15 , 16 ]. Furthermore, having an existing mental health condition such as depression or anxiety may present an additional risk, which may contribute to potential exacerbation of the symptoms or relapsing due to service disruption or the need for isolation [ 13 , 14 , 15 , 16 , 17 ]. The received support during the current pandemic was also a significant protector against mental health symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported numerous mental disorders due to the prevalence of COVID‐19 disease and the effects of quarantine in the community 5 . In Iran, high levels of anxiety, stress, 6 and fear have been reported 7 …”
Section: Introductionmentioning
confidence: 99%
“…5 In Iran, high levels of anxiety, stress, 6 and fear have been reported. 7 According to the World Health Organization (WHO) on April 27, 2020, 109 577 laboratory-confirmed COVID-19 incidents, which included 3809 deaths, were widely reported in China and 28 673 incidents in 104 other countries. 8 Less than half of the patients had underlying diseases such as diabetes, hypertension, and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…According to Keng et al (2011) mindfulness has positive psychological effects such as increasing subjective wellbeing, reducing psychological symptoms and emotional reactivity, and regulating and improving various behaviors associated with mental health and higher levels of life satisfaction. The majority of aspects of mindfulness was related to the experience of meditation as well as psychological symptoms ( Malakoutikhah et al, 2021 ) and wellbeing ( Baer et al, 2008 ). These findings in mindfulness are consistent with the findings of the current study.…”
Section: Discussionmentioning
confidence: 99%